NRG Oncology/RTOG 0921: A phase 2 study of postoperative intensity‐modulated radiotherapy with concurrent cisplatin and bevacizumab followed by carboplatin and paclitaxel for patients with endometrial cancer. Issue 13 (6th April 2015) - Viswanathan, Akila N.; Moughan, Jennifer; Miller, Brigitte E.; Xiao, Ying; Jhingran, Anuja; Portelance, Lorraine; Bosch, Walter R.; Matulonis, Ursula A.; Horowitz, Neil S.; Mannel, Robert S.; Souhami, Luis; Erickson, Beth A.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The current study was conducted to assess acute and late adverse events (AEs), overall survival (OS), pelvic failure, regional failure, distant failure, and disease‐free survival in a prospective phase 2 clinical trial of bevacizumab and pelvic intensity‐modulated radiotherapy (IMRT) with chemotherapy in patients with high‐risk endometrial cancer. METHODS Patients underwent a hysterectomy and lymph node removal, and had ≥1 of the following high‐risk factors: grade 3 carcinoma with >50% myometrial invasion, grade 2 or 3 disease with any cervical stromal invasion, or known extrauterine extension confined to the pelvis. Treatment included pelvic IMRT and concurrent cisplatin on days 1 and 29 of radiation and bevacizumab (at a dose of 5 mg/kg on days 1, 15, and 29 of radiation) followed by adjuvant carboplatin and paclitaxel for 4 cycles. The primary endpoint was grade ≥3 AEs occurring within the first 90 days (toxicity was graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]). RESULTS A total of 34 patients were accrued from November 2009 through December 2011, 30 of whom were eligible and received study treatment. Seven of 30 patients (23.3%; 1‐sided 95% confidence interval, 10.6%‐36.0%) developed grade ≥3 treatment‐related nonhematologic toxicities within 90 days; an additional 6 patients experienced grade ≥3 toxicities between 90 and 365 days after treatment. The 2‐year OS rate was 96.7% and the disease‐free survival rate was 79.1%. No patient developed a within‐field pelvic failure and no patients with International Federation of Gynecology and Obstetrics stage I to IIIA disease developed disease recurrence after a median follow‐up of 26 months. CONCLUSIONS Postoperative bevacizumab added to chemotherapy and pelvic IMRT appears to be well tolerated and results in high OS rates at 2 years for patients with high‐risk endometrial carcinoma. Cancer 2015;121:2156–2163. © 2015 American Cancer Society.